Jak se odrazízájem o téma zdraví a nemocí v užití vybraných kolokací v českých textech - Kolářová, Ivana (Stylistyka, 2020)
Themes of “health” and “illness” háve been always very popular in spoken and written communication in Czech. In the corpora o f spoken Czech the words zdraví (health), nemoc, choroba, and onemocnění (illness) are often infrequent, depending on the smáli range of those corpora. In the corpus o f written texts SYN (1.3 billion words and tokens), words were found in a lot o f thousands seutences. That is wh> we háve decided to research the words zdrávi, nemoc, choroba, onemocněni in the collocations ’adjective + zdraví’, ’adjective + nemoc’, adjective + choroba’, ’adjective + onemocnění’. We presuppose the fřequency o f the collocations can reflect how much attention is paid to the themes of “health” and “illness” (what kind of illness are spoken about, what problems of health are discussed, etc.). Those collocations are ušed in ioumalistic texts, and some ot them háve been found in scientific texts. We háve tried to fínd the fřequency of those collocation reflexes interests o f various themes of health and illness. We found that the use o f the most ťřequent collocations reflect the problems of i lnesses that people are mos mterested in: for example, Alzheimer’s disease, Parkinson’s disease, Creutzfeldt-Jakob disease, in generál mental illnesses, and mental and physical health. The name o f diseases oř the characteristics of illnesses and diseases are onen used in joumalistic texts dealing with medical matters that are intended for laypersons, and that are characterized by persuasive components.